Prevalence and pattern of skin diseases in tribal villages of Gujarat: A teledermatology approach - Rochit Rajesh Singhal (Indian Journal of Community Medicine, 2020)
Background: The prevalence and pattern of skin diseases are influenced by the overall ecosystem of the region. There is a dearth of research about prevalence, health-care seeking, compliance, and treatment outcome in skin diseases among scheduled tribes. Objectives: The aim of this study is to understand the magnitude of skin diseases in tribal area of Dahod, Gujarat using a simple “Store and Forward” technique of teledermatology. Materials and Methods: A cross-sectional study was conducted in 10 randomly selected villages of Dahod and Jhalod blocks of Dahod district of Gujarat during June–August 2017. Trained surveyors visited households randomly in different localities (called Faliya) of each village ensuring representativeness. Survey responses were captured on mobile-based MAGPI portal, and images of skin conditions were capture on smart phones, and de-identified images were transferred over WhatsApp. Results: A total of 781 households were approached in 10 villages and 2214 participants consented. Among them, 549 were identified with suspected skin diseases, but 520 consented for photograph. The skin diseases were more prevalent among males, children, and elderly. Of 520, 44 (8.5%) could not be assess due to poor quality photograph and 35 (6.7%) did not have any clinically significant condition. Thus, of 2214 participants, 441 (20%) had skin diseases, and infections and eczema were major conditions constituting two-third of the skin diseases in the study population. The treatment-seeking behavior and compliance to treatment was poor. Conclusion: Considering the high prevalence of skin diseases in tribal villages of Dahod, Gujarat coupled with limited availability of trained dermatologist, new innovative avenues like teledermatology should be explored.